Analysis of cadmium in infant milk powder using the differential pulse anodic stripping voltammetry - Isa, Siti Zaharah Md (Universiti Sains Malaysia, 2015)
An anodic stripping voltammetric (ASV) technique was used for determination of the cadmium in infant milk powder by using the hanging mercury drop electrode (HMDE). Ten samples of infant milk powder which are suitable from zero to twelve months (one year) from different brands and manufactures from the hypermarket and pharmacies in Kubang Kerian area were bought and analyzed. The samples were digested in nitric acid solution by using microwave high pressure digestion technique at 210 °C. The determination of the cadmium trace elements was made in acetate buffer at pH 4.6 and was stirred at 2000 rpm. The optimize parameters for the voltammetric determination of the cadmium are: initial potential, Et = -0.70 V; final potential, Ef = 0.50 V; deposition potential, Eacc = -1.15 V; deposition time, tacc = 90 s; equilibrium time, teq= 10 s; sweep rate = 0.06 V/s; pulse amplitude = 0.05 V; and purge time = 300 s. Cadmium was not detected in all samples except for samples 9 and 10 which showed the Cd contents were about 12.458 ± 2.899 and 31.517 ± 4.320 ppb respectively. This amount is under limit state by the World Health Organization 1972 about 1 ug/kg/day cadmium for children.